Competency-based approach as a factor of a tourist enterprise effective personnel policy (Economics and region, 2021)
It is explored the theoretical foundations and features of the methodology of implementation the competency-based approach in the training and professional development of tourism professionals. The priority directions of professionalization of success of the expert in the field of tourism are allocated. It is revealed that the use of the competence approach in the management of human resources of a tourist enterprise is the result of a systematic study of the problems of improving the personnel system at modern tourist enterprises. It is emphasized the effectiveness and relevance of the proposed structural and logical model of human resources development management by competency-based approach, which allows to solve existing problems related to the development of competencies, increase productivity and effective performance of duties.
Keywords: tourist enterprise; labor; personnel policy; human resource; competitive specialist; competency-based approach; personnel potential